2021
DOI: 10.1371/journal.pntd.0009689
|View full text |Cite
|
Sign up to set email alerts
|

Location and expression kinetics of Tc24 in different life stages of Trypanosoma cruzi

Abstract: Tc24-C4, a modified recombinant flagellar calcium-binding protein of Trypanosoma cruzi, is under development as a therapeutic subunit vaccine candidate to prevent or delay progression of chronic Chagasic cardiomyopathy. When combined with Toll-like receptor agonists, Tc24-C4 immunization reduces parasitemia, parasites in cardiac tissue, and cardiac fibrosis and inflammation in animal models. To support further research on the vaccine candidate and its mechanism of action, murine monoclonal antibodies (mAbs) ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Building on the knowledge that a balanced immune response correlates with reduced disease symptoms, we developed a vaccine containing recombinant Tc24-C4 protein combined with a TLR4 agonist adjuvant 23,24 . The Tc24 antigen is a T. cruzi flagellar calcium-binding antigen that is conserved across multiple discrete typing units of T. cruzi, and is expressed in extracellular trypomastigote and early intracellular amastigote stages 25,26 . When used as an immunotherapy in experimentally infected mice, the vaccine increased levels of antigen-specific CD8 + cells as well as the key cytokines IFNγ, IL-10, and IL-17A 24,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Building on the knowledge that a balanced immune response correlates with reduced disease symptoms, we developed a vaccine containing recombinant Tc24-C4 protein combined with a TLR4 agonist adjuvant 23,24 . The Tc24 antigen is a T. cruzi flagellar calcium-binding antigen that is conserved across multiple discrete typing units of T. cruzi, and is expressed in extracellular trypomastigote and early intracellular amastigote stages 25,26 . When used as an immunotherapy in experimentally infected mice, the vaccine increased levels of antigen-specific CD8 + cells as well as the key cytokines IFNγ, IL-10, and IL-17A 24,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…One promising vaccine candidate is the T. cruzi flagellar calcium binding protein designated Tc24 ( Dumonteil et al., 2012 ). This antigen is located along the inner leaflet of the flagellar membrane and is highly expressed in the extracellular trypomastigote form as well as in the non-dividing intracellular amastigote form of T. cruzi ( Versteeg et al., 2021 ). Several studies have demonstrated that recombinant protein based vaccines containing Tc24 antigens induce strong immune responses, with increased production of antigen specific CD8+ T cells as well as production of IFN-γ, IL-10 and IL-17A ( Barry et al., 2016 ; Seid et al., 2016 ; Jones et al., 2018 ; Cruz-Chan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A successful vaccine profile is expected to yield a T-helper 1 cell (Th1-type) response, characterized by the production of the pro-inflammatory cytokines IFN-γ, TNF-α, and IL-2, which are crucial for controlling T. cruzi infection, involved in activating immune cells, promoting inflammation, and enhancing the generation of a specific immune response. 46,47 In detail, IFN-γ and TNF-α promote the activation of macrophages and other immune cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%